2019
DOI: 10.7554/elife.40655
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of hypomethylated DNA loci controlling quantitative resistance in Arabidopsis

Abstract: Variation in DNA methylation enables plants to inherit traits independently of changes to DNA sequence. Here, we have screened an Arabidopsis population of epigenetic recombinant inbred lines (epiRILs) for resistance against Hyaloperonospora arabidopsidis (Hpa). These lines share the same genetic background, but show variation in heritable patterns of DNA methylation. We identified four epigenetic quantitative trait loci (epiQTLs) that provide quantitative resistance without reducing plant growth or resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 77 publications
(118 reference statements)
4
98
0
2
Order By: Relevance
“…by which disease-induced DNA hypomethylation is transmitted to following generations to control TAR. This hypothesis is supported by Furci et al (49), who identified hypomethylated DNA regions that control quantitative disease resistance and that are stable over multiple generations. Furthermore, mutation of the DNA demethylase gene ROS1 not only affects basal resistance to biotrophic pathogens (155) but also prevents TAR in progeny from diseased plants (81).…”
Section: Py57ch23_tonmentioning
confidence: 74%
See 2 more Smart Citations
“…by which disease-induced DNA hypomethylation is transmitted to following generations to control TAR. This hypothesis is supported by Furci et al (49), who identified hypomethylated DNA regions that control quantitative disease resistance and that are stable over multiple generations. Furthermore, mutation of the DNA demethylase gene ROS1 not only affects basal resistance to biotrophic pathogens (155) but also prevents TAR in progeny from diseased plants (81).…”
Section: Py57ch23_tonmentioning
confidence: 74%
“…Recent evidence has shown that sRNAs can trans-activate defense-related genes through interaction with ARGONAUTE 1 (AGO1) and the SWI/SNF chromatin remodeling complex (79). Further support for trans-regulation of defense gene priming came from a recent study of Arabidopsis epigenetic recombinant inbred lines (epiRILs), which identified four hypomethylated epigenetic quantitative trait loci (epiQTLs) that control quantitative resistance against downy mildew (49). Transcriptome analysis revealed that the most resistant epiRILs were constitutively primed to activate defense-related genes.…”
Section: Py57ch23_tonmentioning
confidence: 99%
See 1 more Smart Citation
“…A binomial distribution test was performed to identify 5mC for each C site, and then the P value of binomial distribution test was subjected to false discovery rate (FDR) correction using the Benjamini & Hochberg method in the p.adjust package of the R software. The C site with coverage > 4X and an FDR < 0.05 was considered to be a true methylation site (Zhang et al, 2017b;Furci et al, 2019).…”
Section: Mapping Reads To the Reference Genomementioning
confidence: 99%
“…Genomes of met1 mutants are largely hypomethylated at CG dinucleotides that usually inherit cytosine methylation faithfully during DNA replication through MET1 activity (5) . Phenotypic abnormalities do, however, not require whole-genome changes in cytosine methylation, as a recent study describes how hypomethylation at a few select loci is sufficient to establish quantitative resistance to a pathogenic oomycete, Hyaloperonospora arabidopsidis (Hpa) (6) .…”
Section: Introductionmentioning
confidence: 99%